ART AS A SOURCE OF FORMATION ARTISTIC PERSPECTIVE OF PERSONALITY (Pedagogy of Higher and Secondary Education, 2022)
Art as a source o f forming o f artistic outlook of personality. The article is devoted to artistic development of personality, especially to forming of its artistic outlook. Special attention is paid to abilities of art as the basis of forming of artistic outlook of personality.